Service Learning for Linguistic and Cultural Diversity in Higher Education: Proposals for Pre-Service (Language) Teacher Education - Joana Duarte; Nadia Gerritsen; Mónica Lourenço; Sílvia Melo-Pfeifer; Susana Pinto (MDPI AG, 2024)
Service learning, an educational methodology that intertwines community service with academic instruction, is garnering growing recognition within higher education due to its potential to enrich both research and outreach efforts. By integrating service learning into the curriculum, higher education institutions (HEIs) can bridge the gap between research and praxis, effectively bringing research findings to local communities and influencing on-the-ground practices. While the benefits of service learning have been widely acknowledged in the literature, there remains a lack of understanding on how service learning can be integrated into teacher education programmes to support linguistic and cultural diversity at schools. Additionally, there is limited insight into how institutions engaged in social action perceive their collaboration with HEIs, particularly in the context of teacher education. In this contribution, we address these gaps, by presenting the results of a multimethod and multisite research study that aimed to explore the perspectives of social action initiatives on the potential collaboration with HEIs to promote (language) teacher education focused on linguistically and culturally responsive practices. The results point to a great heterogeneity of social action projects and expectations on the part of the institutions regarding collaboration with HEIs. Despite this diversity, common principles of collaboration emerge from the data. These principles lay the foundations for a framework that may shape collaborative efforts between HEIs and social action initiatives in the field of pre-service (language) teacher education with the goal of promoting pedagogies that respect and leverage linguistic and cultural diversity in multilingual settings.